Waterproof composite material for tunnel engineering and preparation method thereof

By adding HIPS, long carbon chain semi -aromatic nylon fiber and crystal beard to the polypropylene/nylon 6 alloy material, and using specific functional auxiliary agents, the mechanical performance and lack of corrosion resistance of polypropylene/nylon 6 alloy materials are solved The problem realizes the high -powered properties and corrosion resistance of authentic waterproof composite materials for authentic engineering.

CN118599228BActive Publication Date: 2025-01-24QINGDAO URBAN CONSTR GRP CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411013960.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-26
Publication Date
2025-01-24
Estimated Expiration
2044-07-26

AI Technical Summary

Technical Problem

The existing polypropylene/nylon 6 alloy materials have shortcomings in terms of mechanical properties and corrosion resistance, and it is difficult to meet the high requirements of waterproof materials for authentic engineering.

Method used

Adopt polypropylene, PA6 powder, and HIPS as the substrate resin, and long carbon chain semi -aromatic nylon fiber and crystal must be used as enhanced fillers, and coupling agents, compatible agents and lubricants are added. Project for waterproof composite materials.

Benefits of technology

It significantly improves the mechanical properties and corrosion resistance of composite materials, and forms a dense structure to prevent corrosive liquid erosion and meet the specific application needs of waterproof materials for authentic engineering.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 86ZVTZ3P1SZ2IDMRASBO5HUNY2SPZZGMXIIN9XMQ
    Figure 86ZVTZ3P1SZ2IDMRASBO5HUNY2SPZZGMXIIN9XMQ
  • Figure B8KDL2YWJBVX0GI04BWI7KHYG7NEZ2XZ5YRQSFTA
    Figure B8KDL2YWJBVX0GI04BWI7KHYG7NEZ2XZ5YRQSFTA
  • Figure HLNDYUGCT6IJGVF4YVM9KR5Z7CNQWHFNQLLAW17W
    Figure HLNDYUGCT6IJGVF4YVM9KR5Z7CNQWHFNQLLAW17W
Patent Text Reader

Abstract

The invention belongs to the technical field of polypropylene alloy materials, and particularly relates to a waterproof composite material for tunnel engineering and a preparation method thereof, comprising the following components in parts by weight: 80-100 parts of polypropylene, 30-40 parts of PA6 powder, 10-20 parts of HIPS, 10-15 parts of long carbon chain semi-aromatic nylon fibers, 6-18 parts of whiskers, 3-8 parts of coupling agents, 3-8 parts of compatibilizers, and 1-5 parts of lubricants. During the composite material blending process, the long carbon chain semi-aromatic nylon fibers and whiskers will be intertwined to form a mesh structure, and the PA6 dispersed in the polypropylene matrix plays the role of a rivet, which can fix the long carbon chain semi-aromatic nylon fibers, so that the polypropylene, the PA6 matrix and the long carbon chain semi-aromatic nylon fibers and whiskers are interconnected to form an organic whole, and there is an acting force between each other to form a dense structure, which greatly improves the mechanical properties and anti-corrosion properties of the composite material and meets the needs of the specific application of the waterproof composite material for tunnel engineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polypropylene alloy materials, and particularly relates to a special waterproof composite material for tunnel engineering and a preparation method thereof. Background Art

[0002] Polypropylene is a thermoplastic resin that is non-toxic, low in density, light in weight, high in strength, heat-resistant, chemically resistant, with excellent molding and processing performance, recyclable, and environmentally friendly. It is widely used in the fields of chemical industry, new building materials, automobiles, home appliances, packaging, etc. According to different polymerization processes, PP can be divided into homopolymer polypropylene (PPH), block copolymer polypropylene (PPB) and random copolymer polypropylene (PPR). The stiffness of PPH, PPB and PPR resins decreases in turn, and the impact resistance increases in turn.

[0003] Polypropylene has high regularity of molecular chain and good high temperature resistance, but poor impact resistance and light aging resistance. It is widely used in the field of tunnel engineering waterproofing, especially in the field of waterproof woven sandbags. The prior art generally uses resin as the main structure of woven bags. Among them, polyethylene and polypropylene have become the preferred materials for woven bags due to their excellent mechanical properties and anti-corrosion properties. Polypropylene has the advantages of low density, low price, low water absorption and easy processing. However, compared with engineering plastics such as polyamide, polypropylene also has the disadvantages of low mechanical properties and insufficient toughness, so it is difficult to apply to certain fields with high requirements for mechanical properties. In order to overcome the inherent shortcomings of polypropylene, blending polypropylene with polyamide to prepare alloys is an ideal solution. The prior art has a technology that blends polypropylene and nylon 6 and uses maleic anhydride compatibilizer to improve the compatibility of the two, so that the material has good tensile, bending and impact properties, and also has a low water absorption rate. However, the long-term corrosion resistance of polypropylene and polyamide is poor. The degree to which maleic anhydride compatibilizer improves the compatibility of polypropylene and nylon 6 is also limited, and it is unable to further improve the mechanical properties of polypropylene / nylon 6 alloy materials and improve the corrosion resistance of the alloy materials. Summary of the invention

[0004] The purpose of the present invention is to overcome the problems of low strength, poor toughness and corrosion resistance of polypropylene / nylon 6 in the prior art, and to provide a special waterproof composite material for tunnel engineering to meet the specific application needs of special waterproofing for tunnel engineering.

[0005] In order to achieve the above object, the present invention provides a special waterproof composite material for tunnel engineering, comprising the following components in parts by weight:

[0006] Polypropylene 80-100 parts, PA6 powder 30-40 parts, HIPS 10-20 parts, long carbon chain semi-aromatic nylon fiber 10-15 parts, whiskers 6-18 parts, coupling agent 3-8 parts, compatibilizer 3-8 parts, lubricant 1-5 parts.

[0007] HIPS is high-impact polystyrene with good toughness, good fluidity and strong corrosion resistance. The addition of HIPS can greatly increase the mechanical strength and corrosion resistance of the composite material.

[0008] In order to improve the mechanical strength and toughness of the composite material, the present invention selects to add long carbon chain semi-aromatic nylon fiber and whisker as reinforcing filler. Long carbon chain semi-aromatic nylon fiber is an organic fiber, which is a polyamide material like PA6 and has good compatibility. During the melt processing, the long carbon chain semi-aromatic nylon fiber and the whisker with better toughness are intertwined to form a network structure, and the long carbon chain semi-aromatic nylon fiber with good compatibility with the matrix nylon resin helps the whisker to be fully dispersed in the matrix resin, prevents the separation of the whisker and the matrix resin, and improves the compactness and mechanical properties of the composite material. Due to the large rigidity of glass fiber, broken wires are prone to occur during melt blending, and its rigid structure is not easy for the polyamide fibers with higher flexibility to be intertwined into a mesh structure, so that the fibrous filler and the resin cannot form an organic whole, and the mechanical properties are poor.

[0009] There is a synergistic effect between the polypropylene and PA6 matrix of the present application and the long carbon chain semi-aromatic nylon fibers and whiskers. Pure polypropylene has poor compatibility with long carbon chain semi-aromatic nylon fibers and whiskers. Although adding coupling agents and compatibilizers can improve the compatibility of polypropylene composite materials to a certain extent, it still cannot meet the requirements of high mechanical properties. On this basis, the introduction of a small amount of PA6 can improve the compatibility of long-chain semi-aromatic nylon fibers, whiskers and polypropylene: during melt blending, nylon 6 is dispersed in the polypropylene matrix. Since long-chain semi-aromatic nylon fibers and nylon 6 belong to the same nylon, they have good compatibility. During the processing, the active groups of the two can react with each other or form hydrogen bonds, which strengthens the interaction between the long-chain semi-aromatic nylon fibers and the nylon 6 matrix. During the blending of the composite materials, the long-chain semi-aromatic nylon fibers and whiskers will be entangled with each other to form a network structure, and the PA6 dispersed in the polypropylene matrix acts as a rivet, which can fix the long-chain semi-aromatic nylon fibers, thereby connecting the polypropylene, PA6 matrix and the long-chain semi-aromatic nylon fibers and whiskers to form an organic whole. There is a force between them to form a dense structure, which greatly improves the mechanical properties and corrosion resistance of the composite materials.

[0010] In one embodiment, the polypropylene is one or more of homopolymer polypropylene and copolymer polypropylene.

[0011] In one embodiment, the long carbon chain semi-aromatic nylon fiber is prepared by melt spinning and is at least one of PA9T, PA10T, PA11T, PA12T, PA16T, PA10I or PA14I. The long carbon chain semi-aromatic nylon fiber has a length of 5mm-20mm and a diameter of 2-5μm.

[0012] In one embodiment, the whiskers are selected from one or more of potassium titanate whiskers, zinc oxide whiskers, calcium sulfate whiskers, aluminum borate whiskers, basic magnesium sulfate whiskers, and calcium carbonate whiskers. The whisker length is 50-300 μm and the diameter is 2-5 μm. Furthermore, the whiskers are 10-15 parts. When the whisker content is small, it is difficult to play an interactive reinforcement role; when the amount is too much, it is not only difficult to disperse, but also may cause floating fiber phenomenon, which is not conducive to improving performance.

[0013] In one embodiment, the coupling agent is selected from one or more of silane coupling agent KH550, silane coupling agent KH560, titanate coupling agent, phosphate coupling agent or aluminate coupling agent.

[0014] In one embodiment, the compatibilizer is one or more of PP-maleic anhydride graft, ethylene-maleic anhydride-glycidyl methacrylate copolymer, ethylene-acrylate-glycidyl methacrylate copolymer and ethylene-acrylate-maleic anhydride copolymer.

[0015] In one embodiment, the lubricant is one or more of ethylene wax, calcium stearate, stearic acid or amide wax.

[0016] The present invention also provides a method for preparing a special waterproof composite material for tunnel engineering, which is characterized by comprising the following steps:

[0017] (1) mixing long carbon chain semi-aromatic nylon fibers and whiskers uniformly to obtain a mixture A;

[0018] (2) Polypropylene, PA6, HIPS, coupling agent, compatibilizer, and lubricant are fed into an extruder from a main feed port, and mixture A is added from a side feed port. After melting, mixing, and homogenizing, the mixture is extruded and granulated to obtain the waterproof composite material for tunnel engineering; the extrusion screw of the extruder has an aspect ratio of 36-48:1.

[0019] In one embodiment, the extrusion temperature of the extruder is controlled at 230-250° C., and the screw speed is controlled at 400-600 r / min.

[0020] Compared with the prior art, the present invention has the following technical advantages: using polypropylene, PA6 powder, and HIPS as matrix resins, and long carbon chain semi-aromatic nylon fibers and whiskers as reinforcing fillers, the composite material is endowed with higher mechanical properties, and the formation of a dense structure can effectively prevent the erosion of corrosive liquids and improve the corrosion resistance of the material. The composite material of the present invention has a simple production process and low preparation cost, and provides a practical and effective solution for the functionalization and differentiation of polypropylene materials. DETAILED DESCRIPTION

[0021] Below in conjunction with specific embodiment, further elaborate content of the present invention.It should be emphasized that these embodiments are only used for further explanation of the present invention, and can not be interpreted as limiting the scope of protection of the present invention.In addition, it should be understood that after reading the content described in the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope limited by the appended claims of the application.

[0022] The formulas of the embodiments and comparative examples provided by the present invention (unit: parts by weight) are shown in Tables 1 and 2 below:

[0023]

[0024] Unless otherwise specified, the types of raw material components in the embodiments and comparative examples are consistent, and the specific components are as follows:

[0025] Polypropylene, PA6 powder, HIPS, whiskers, coupling agent, compatibilizer, and lubricant are all commercially available; PA12T and PPTA fibers are prepared by melt spinning, specifically:

[0026] The polypropylene is copolymer polypropylene;

[0027] The long carbon chain semi-aromatic nylon fiber is prepared by melt spinning and is PA12T, with a length of about 10 mm and a diameter of 3 μm. The PPTA fiber is prepared by melt spinning and has a length of about 10 mm and a diameter of 3 μm.

[0028] The whiskers are calcium sulfate whiskers with a length of about 100 μm and a diameter of 4 μm.

[0029] The coupling agent is KH550;

[0030] The compatibilizer is maleic anhydride grafted PP;

[0031] The lubricant is calcium stearate.

[0032] According to the formulas in Tables 1 and 2, the raw material components in the examples and comparative examples were used in accordance with the following preparation method to prepare a waterproof composite material for tunnel engineering, the preparation steps being:

[0033] (1) mixing long carbon chain semi-aromatic nylon fibers and whiskers uniformly to obtain a mixture A;

[0034] (2) Polypropylene, PA6, HIPS, coupling agent, compatibilizer, and lubricant are fed into the extruder from the main feed port, and the mixture A is added from the side feed port, and the mixture is melted, mixed, homogenized, and then extruded and granulated to obtain the waterproof composite material for tunnel engineering. The extrusion screw of the extruder has a length-to-diameter ratio of 40:1; the extrusion temperature of the extruder is controlled at 240° C., and the screw speed is controlled at 500 r / min.

[0035] The tunnel engineering waterproof composite materials prepared in the examples and comparative examples were injection molded into standard samples. Under the same test conditions, the sample tensile strength MPa (ASTM D 638), flexural strength MPa (ASTM D 790), notched impact strength kJ / m 2 (ISO179) and appearance (grade 1-5, the higher the grade, the smoother the surface of the pattern) and other performance indicators were tested; at the same time, the special waterproof composite material for tunnel engineering prepared in the embodiment and the comparative example was added to a flat wire machine, extruded, cut into embryonic wires, stretched, and then woven into cloth; the weight loss rate (Dw) (%, the mass change rate of the woven cloth before and after immersion) and the size change rate (Dt) (%, the size change rate of the woven cloth before and after immersion) of the woven cloth after being immersed in highly mineralized groundwater for three months were tested, as shown in Tables 3 and 4 below.

[0036]

[0037]

[0038] From Comparative Examples 1-7 and Examples 1-10, it can be seen that the addition of HIPS improves the mechanical properties and corrosion resistance of polypropylene composite materials, improves the product appearance, and reduces the floating fiber phenomenon. This may be because HIPS has a low Vicat softening point (generally 90-110°C), is easier to soften and melt during the melt processing, and has good fluidity, and is easier to flow to the surface of the composite material to form a dense outer layer structure, avoiding the occurrence of floating fiber phenomenon; when used in a high-salt environment, the dense structure can prevent various ions from entering the interior of the composite material, playing a shielding and protective role.

[0039] It can be seen from Comparative Examples 1-7 and Example 7 that there is a synergistic effect between the polypropylene and PA6 matrix of the present application and the long carbon chain semi-aromatic nylon fibers and whiskers. A small amount of PA6 can improve the compatibility of the long carbon chain semi-aromatic nylon fibers, whiskers and polypropylene. During the blending process of the composite material, the long carbon chain semi-aromatic nylon fibers and whiskers will be entangled with each other to form a mesh structure, so that the polypropylene, PA6 matrix and the long carbon chain semi-aromatic nylon fibers and whiskers are interconnected to form an organic whole, and there is a force between them to form a dense structure, which greatly improves the mechanical properties and anti-corrosion properties of the composite material.

[0040] It can be seen from Comparative Example 3 and Example 7 that since the semi-aromatic polyamide introduces aromatic rings and long chain structures in the molecular chain, it has higher mechanical strength and toughness, as well as good chemical corrosion resistance and lower water absorption. Although traditional commercial aramid nylon fiber has high strength and high modulus, its rigidity is too large and it is not easy to entangle with the flexible whiskers to form a dense network structure, and cannot meet the use requirements.

[0041] It can be seen from Comparative Example 5 and Example 7 that the mechanical and anti-corrosion properties of long carbon chain semi-aromatic nylon fibers are inferior to those of whiskers. When long carbon chain semi-aromatic nylon fibers are used alone as reinforcing fillers, they cannot play a synergistic reinforcing and toughening role.

[0042] It can be seen from Comparative Examples 6-7 and Example 7 that the amount of polyamide fiber used for connection should not be too little or too much. Too little will not play an effective riveting role, while too much will lead to uneven dispersion and floating fiber phenomenon, which not only affects the appearance of the material, but also makes the surface of the material rough and has pits, which is easy to drain the solution to invade and erode.

[0043] In summary, the present invention uses polypropylene, PA6 powder, and HIPS as matrix resins, long carbon chain semi-aromatic nylon fibers and whiskers as reinforcing fillers, and adds a certain amount of coupling agents, compatibilizers, lubricants and other functional additives, which can greatly improve the mechanical properties and corrosion resistance of polypropylene-based composite materials, and meet the specific application needs of special waterproof materials for tunnel engineering.

[0044] Although the present invention has been described in detail above by general description and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements can be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all belong to the scope of protection claimed by the present invention.

Claims

1. A waterproof composite material specially used for tunnel engineering, characterized in that: Contains the following components in parts by weight: 80-100 parts of polypropylene, 30-40 parts of PA6 powder, 10-20 parts of HIPS, 10-15 parts of long carbon chain semi-aromatic nylon fiber, 6-18 parts of whiskers, 3-8 parts of coupling agent, 3-8 parts of compatibilizer and 1-5 parts of lubricant; the long carbon chain semi-aromatic nylon fiber is prepared by melt spinning and is selected from at least one of PA9T, PA10T, PA11T, PA12T, PA16T, PA10I and PA14I; the long carbon chain semi-aromatic nylon fiber has a length of 5mm-20mm and a diameter of 2-5μm.

2. The waterproof composite material for tunnel engineering as claimed in claim 1, characterized in that: The polypropylene is one or more of homopolymer polypropylene and copolymer polypropylene.

3. The waterproof composite material for tunnel engineering as claimed in claim 1, characterized in that: The whiskers are selected from one or more of potassium titanate whiskers, zinc oxide whiskers, calcium sulfate whiskers, aluminum borate whiskers, basic magnesium sulfate whiskers, and calcium carbonate whiskers; the whiskers have a length of 50-300 μm and a diameter of 2-5 μm.

4. The waterproof composite material for tunnel engineering as claimed in claim 1, characterized in that: The coupling agent is selected from one or more of silane coupling agent KH550, silane coupling agent KH560, titanate coupling agent, phosphate coupling agent or aluminate coupling agent.

5. The waterproof composite material for tunnel engineering as claimed in claim 1, characterized in that: The compatibilizer is one or more of PP-maleic anhydride graft, ethylene-maleic anhydride-glycidyl methacrylate copolymer, ethylene-acrylate-glycidyl methacrylate copolymer and ethylene-acrylate-maleic anhydride copolymer.

6. The waterproof composite material for tunnel engineering as claimed in claim 1, characterized in that: The lubricant is one or more of polyethylene wax, calcium stearate, stearic acid or amide wax.

7. The method for preparing the special waterproof composite material for tunnel engineering according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) mixing long carbon chain semi-aromatic nylon fibers and whiskers uniformly to obtain a mixture A; (2) Polypropylene, PA6, HIPS, coupling agent, compatibilizer, and lubricant are fed into an extruder from a main feed port, and mixture A is added from a side feed port. After melting, mixing, and homogenizing, the mixture is extruded and granulated to obtain a waterproof composite material for tunnel engineering; the extrusion screw of the extruder has an aspect ratio of 36-48:

1.

8. The method for preparing the special waterproof composite material for tunnel engineering as claimed in claim 7, characterized in that: The extrusion temperature of the extruder is controlled at 230-250° C., and the screw speed is controlled at 400-600 r / min.

Citation Information

Patent Citations

  • High dielectric property polypropylene / nylon / whisker composite material and preparation method thereof

    CN106380678A

  • Glass fiber reinforced polypropylene / nylon 6 alloy material and preparation method thereof

    CN109776952A